Outage analysis in presence of correlated interferers in a cognitive radio – CDMA network. (1st January 2012) - Dhar Roy, Sanjay; Kundu, Sumit
In this paper, the outage performance of a primary user (PU) is evaluated analytically in presence of a large number of secondary users (SUs) in an underlay spectrum sharing architecture. We consider cognitive users in ad hoc mode using the spectrum licensed for a cellular CDMA network. We develop an analytical framework for evaluation of downlink interference in our proposed cognitive radio CDMA (CR-CDMA) networking model. A closed form expression for the probability of outage for a PU assuming correlation amongst interferences caused by co-channel BSs and SUs has been derived. We study the impact of SUs and several other parameters (of channel and network) on the outage probability for a PU. Analytical results are validated with simulation results.